"Cat got your lung?": Case of a trapped lung following cat bite. (2019) - Walayat, Saqib; Asghar, M.; Horvath, Emily; Farrell, John J.
Abstract: Pasturella multocida is a gram negative encapsulated facultative bacillus that has been reported to cause a wide variety of infections in humans. Empyema is rarely reported complication of P. multocida infection. Infection is usually acquired by inhalation or bite from a domestic animal, with cats and dogs being the most common sources. Isolation of organisms on culture remains gold standard for diagnosis. We describe a case of P. multocida related empyema in a patient who subsequently developed trapped lung requiring video assisted thoracoscopic surgical decortication. It was determined that the cause of this patient's empyema was likely from a bite from his own cat.